Systematic Review of Dairy Processing Sludge and Secondary STRUBIAS Products Used in Agriculture - Hu, Yihuai; Khomenko, Olha; Shi, Wenxuan; Velasco-Sánchez, Ángel; Ashekuzzaman, S. M.; Bennegadi-Laurent, Nadia; Daly, Karen; Fenton, Owen; Healy, Mark G.; Leahy, J. J.; Sørensen, Peter; Sommer, Sven G.; et al. (Frontiers in Sustainable Food Systems, 2021)
Worldwide dairy processing plants produce high volumes of dairy processing sludge (DPS), which can be converted into secondary derivatives such as struvite, biochar and ash (collectively termed STRUBIAS). All of these products have high fertilizer equivalent values (FEV) but future certification as P-fertilizers in the European Union will mean they need to adhere to new technical regulations for fertilising materials i.e. content limits pertaining to heavy metals (Cd, Cu, Hg, Ni, Pb and Zn) and individual European countries have set limits for synthetic organic compounds and pathogens. This review presents our current state of knowledge pertaining to these bio-based fertilizers and identifies knowledge gaps. In addition a review and calculation of greenhouse gas emission (GHG) from a range of concept dairy sludge management, production and management systems for STRUBIAS products (i.e. biochar from pyrolysis and hydrochar from hydrothermal carbonification (HTC)) were examined. Results from the initial review showed that DPS contents depend on product type and treatment processes at a given processing plant, which leads to varied nutrient, heavy metal and carbon profiles. These products are all typically high in nutrients and carbon but low in heavy metals. Further work needs to concentrate on examining their pathogenic microorganism and emerging contaminant profiles. Specifically with respect to STRUBIAS products contaminants not present in the raw DPS may need further treatment before being land applied in agriculture e.g. heated producing ashes, hydrochar or biochar. An examination of these products from an environmental perspective shows that their water quality footprint could be minimised using application rates based on phosphorus (P), incorporation of these products into nutrient management planning and application using incorporation into the soil. Results from the concept system work showed that elimination of methane emissions was possible along with a reduction in nitrous oxide (N2O). Less carbon is transferred to agricultural fields where DPS is processed into biochar and hydrochar, but due to high recalcitrance the C in this form is retained much longer in the soil, and therefore STRUBIAS products represents a more stable and long term option to increase soil C stocks and sequestration.